MODIFIKASI AKSES PINTU MENGGUNAKAN KARTU DENGAN CONTROL DAN MONITOR JARAK JAUH DI LABORATORIUM AIRFIELD GROUND LIGHTING SEKOLAH TINGGI PENERBANGAN INDONESIA - Halmi Safeti Yoga; Nurhedhi Desryanto; Inof Seno Acton (Langit Biru: Jurnal Ilmiah Aviasi, 2020)
In the area of Indonesian Civil Aviation Institute there is an Airfield Ground Lighting Laboratory building. Inside the building there are practice materials / tools that have high selling points. But now the door access in the building is still using a key. The author will modify the door access by using a card with a control and monitor using SMS. Several tools and materials, including: RFID RC522, GSM A6 Ai-Thinkers Module, buzzer, LCD with I2C module, LED and door lock solenoid. As a result of modifying the access door using the delivery card, it can minimize theft in the building, limit the users of the building (Restricted Area), limit the use of the building so as not to exceed the time limit.